Design of a fuzzy Takagi-Sugeno controller to vary the joint knee angle of paraplegic patients - Teixeira, Marcelo C. M.; Deaecto, Grace S.; Gaino, Ruberlei; Assuncao, Edvaldo; Carvalho, Aparecido A.; Farias, Uender C. (Springer, 2006)
The papers shows, through theoretical studies and simulations, that using the description of the plant by Takagi-Sugeno (T-S), it is possible to design a nonlinear controller to control the position of the leg of a paraplegic patient. The control system was designed to change the angle of the joint knee of 60 degrees. This is the first study that describes the application of Takagi-Sugeno (T-S) models in this kind of problem.
Keywords: Takagi-Sugeno fuzzy models; nonlinear control; paraplegia; rehabilitation engineering; Functional Electrical Stimulation